2021
DOI: 10.1124/dmd.120.000297
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Analysis of the Postmitochondrial Supernatant Fraction of Human Lens-Free Whole Eye and Liver

Abstract: The increasing incidence of ocular diseases has accelerated research into therapeutic interventions needed for the eye. Ocular enzymes play important roles in the metabolism of drugs and endobiotics. Various ocular drugs are designed as prodrugs that are activated by ocular enzymes. Moreover, ocular enzymes have been implicated in the bioactivation of drugs to their toxic metabolites.The key purpose of this study was to compare global proteomes of the pooled samples of the eye (n 5 11) and the liver (n 5 50) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…To probe the effect of CYP2E1 modification by benzophenone derivatives on the functional properties of the enzyme, we incorporated CYP2E1-BPM and CYP2E1-BPS into insect cell microsomes (Supersomes TM ) containing cDNA-expressed human NADPH-cytochrome P450 reductase (CPR) along with human cytochrome b 5 (SS(CPR+b5)) and studied their activity in deethylation of 7-Ethoxy-4-trifluoromethylcoumarin (7-EFC). Although this fluorogenic substrate is commonly used as a CYP2B6-specific probe, it can also be metabolized by CYP2E1 with a reasonable turnover rate [ 25 , 33 , 34 ]. To obtain the appropriate reference points, we also studied 7-EFC metabolism by SS(CPR+b5) with incorporated unmodified CYP2E1 (SS(CPR+b5)2E1) and commercial preparation of Supersomes containing cDNA-expressed full-length CYP2E1 (SS(2E1)).…”
Section: Resultsmentioning
confidence: 99%
“…To probe the effect of CYP2E1 modification by benzophenone derivatives on the functional properties of the enzyme, we incorporated CYP2E1-BPM and CYP2E1-BPS into insect cell microsomes (Supersomes TM ) containing cDNA-expressed human NADPH-cytochrome P450 reductase (CPR) along with human cytochrome b 5 (SS(CPR+b5)) and studied their activity in deethylation of 7-Ethoxy-4-trifluoromethylcoumarin (7-EFC). Although this fluorogenic substrate is commonly used as a CYP2B6-specific probe, it can also be metabolized by CYP2E1 with a reasonable turnover rate [ 25 , 33 , 34 ]. To obtain the appropriate reference points, we also studied 7-EFC metabolism by SS(CPR+b5) with incorporated unmodified CYP2E1 (SS(CPR+b5)2E1) and commercial preparation of Supersomes containing cDNA-expressed full-length CYP2E1 (SS(2E1)).…”
Section: Resultsmentioning
confidence: 99%
“…Our quantitative data confirms this ocular profile for CES1 and AADAC, but in contrast, clearly indicates the presence of CES2. Another qualitative study indicated the presence of CES4/CES1P1 while no other CES isoform was identified in the S9 fraction from pooled human whole eyes (Balhara et al, 2021). This sampling approach minimized interindividual variation but diluted the individual tissue contents.…”
Section: Discussionmentioning
confidence: 97%
“…RPE/choroid (Skeie and Mahajan, 2014). In contrast, a recent study identified only CES4/CES1P1 among CES isoforms in S9 fractions of pooled human eye homogenates (Balhara et al, 2021). Such qualitative data cannot fully estimate the metabolic profile of human eye tissues.…”
mentioning
confidence: 89%
“…After washing and drying, the gel fragments were subjected to trypsin digestion using a previously described procedure [22]. MS analysis was carried out using a nanoLC coupled to a Q Exactive HF hybrid quadrupole-orbitrap™ mass spectrometer (Thermo Fisher Scientific, Rockwell, IL, USA) [30]. The obtained raw data were processed using the MaxQuant software (https://maxquant.org) with the built-in search engine Andromeda.…”
Section: Methodsmentioning
confidence: 99%
“…Following subsequent treatment with 55 mM iodoacetamide in 0.1 M ammonium bicarbonate in the dark at room temperature for 20 min, the gel fragments were dried with pure acetonitrile and digested with trypsin as described in [29]. Further LC-MS/MS analysis was carried out using nanoLC coupled to a Q Exactive HF hybrid quadrupole-orbitrap™ mass spectrometer (Thermo Fisher Scientific, Rockwell, IL, USA) [30].…”
Section: Untargeted Proteomics Assaysmentioning
confidence: 99%